2019
DOI: 10.1038/s41598-019-47734-z
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the P2X7 receptor in the migration and metastasis of tamoxifen-resistant breast cancer: effects on small extracellular vesicles production

Abstract: Tamoxifen (TAM) is the standard anti-hormonal therapy for estrogen receptor-positive breast cancer. However, long-term TAM therapy can make acquisition of TAM resistance and there are still no solutions to treat TAM-resistant breast cancer. In this study, we found that protein and mRNA expression of the P2X purinoreceptor 7 (P2X7) was higher in tamoxifen resistant MCF-7 (TAMR-MCF-7) cells than in control MCF-7 cells. P2X7 inhibition potently inhibited the migration of TAMR-MCF-7 cells and the liver metastasis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 50 publications
1
40
0
Order By: Relevance
“…GPR120 as a GPCR is mainly coupled with Gαq protein [3,4,5]. To investigate the GPR120 agonist activities of the isolated 25 triterpenoids, we examined the Gαq-mediated intracellular calcium ([Ca 2+ ]i) release after exposing hGPR120-CHO cells to a known GPR120 agonist, GW-9508, or to the isolated components (Figure 2a) [18]. The intracellular calcium ([Ca 2+ ]i) was significantly increased by five natural triterpenoids, namely, S4 , S7 , S12 , 3- O -Protocatechuoylceanothic acid ( 1 ) , and S16 ; the other components did not have any significant effects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GPR120 as a GPCR is mainly coupled with Gαq protein [3,4,5]. To investigate the GPR120 agonist activities of the isolated 25 triterpenoids, we examined the Gαq-mediated intracellular calcium ([Ca 2+ ]i) release after exposing hGPR120-CHO cells to a known GPR120 agonist, GW-9508, or to the isolated components (Figure 2a) [18]. The intracellular calcium ([Ca 2+ ]i) was significantly increased by five natural triterpenoids, namely, S4 , S7 , S12 , 3- O -Protocatechuoylceanothic acid ( 1 ) , and S16 ; the other components did not have any significant effects.…”
Section: Resultsmentioning
confidence: 99%
“…The increase in GPR120-mediated intracellular Ca 2+ was measured by the [Ca 2+ ] FLIPR assay as described previously [18]. Briefly, CHO cells overexpressing hGPR120 (hGPR120-CHO) and Gα16 (Gα16-CHO) were seeded (5 × 10 4 cells of each type) in 96-well plates and cultured overnight.…”
Section: Methodsmentioning
confidence: 99%
“…Although the initial response to tamoxifen is satisfactory, the majority of patients develop resistance and tumor progression (5). Moreover, tamoxifen-resistant (TAMR) breast cancer is more prone to invasion and metastasis (6), thus the 5-year survival rate of patients with breast cancer drops from 80 to 27% with the occurrence of distant metastasis (7).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies [10][11][12] have shown that extracellular ATP is likely to be an important invasive factor in TME. The ATP-gated receptor P2X7 is expressed in multiple malignant tumours, including breast cancers [13]. Furthermore, it has been reported that P2X7R is the key mediator of ATP to promote the invasion of cancer growths [14].…”
Section: Introductionmentioning
confidence: 99%